Energy-Harvesting Smart Tiles for Human–Machine Interface Applications - Alessandro Zompanti; Paolo Romeo; Anna Sabatini; Luca Vollero; Marco Santonico; Giorgio Pennazza (Proceedings)
In this work, a human–machine interface with energy harvesting capabilities was developed and a modular floor made of tiles equipped with piezoelectric elements was produced. The developed platform was tested as a position-tracking system for a human user, allowing the tracking of the lower body in a virtual reality environment. Moreover, the energy collected by the device was evaluated.